IMPROVING THE STUDENTS’ WRITING SKILL BY USING SHELTERED INSTRUCTION OBSERVATION PROTOCOL (SIOP) - Mallapiang, Yasser (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2015)
This research aimed at finding out the improvement of the students’  ability in writing specially for narrative text in terms of grammar and vocabulary by using Sheltered Instruction Observation Protocol (SIOP) model.The researcher used a Classroom Action Research (CAR) to explain the improvement which was conducted in two cycles in which every cycle consisted of four meetings. The location of this research was taken at thesecond year of Senior High School Muhammadiyah 2 Kapopposang Makassarwith the number of the subject i.e. 22 students. The data analyze shows thatthe application of SIOP model issignificant in improving the students’ writing ability in terms of grammar and vocabulary. It is proved by the mean score of cycle I is 6,11 then improved to be 7,22 in cycle II. They are higher than the mean score of diagnostic test namely 5,69. It means that there is the improvement of the students’ writing ability in terms of grammar and vocabulary in narrative text. Based on the findings above, the researcher made conclusion that by application SIOP Model could improve the students’ writing skill achievement in narrative text.